2017
DOI: 10.18632/oncotarget.19553
|View full text |Cite
|
Sign up to set email alerts
|

Added value of diffusion weighted imaging in pediatric central nervous system embryonal tumors surveillance

Abstract: Diffusion weighted imaging (DWI) has an established role in primary CNS embryonal tumor (ET) characterization; however, its diagnostic utility in detecting relapse has never been determined. We aimed to compare DWI and conventional MRI sensitivity in CNS ET recurrence detection, and to evaluate the DWI properties of contrast-enhancing radiation induced lesions (RIL).Fifty-six patients with CNS ET (25 with disease relapse, 6 with RIL and 25 with neither disease relapse nor RIL) were retrospectively evaluated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…An even greater accuracy can be achieved by combining DWI and MRS to obtain more information about the tumour proliferative potential [ 48 ]. DWI has also been reported to be useful in detecting relapse of embryonal tumours such as medulloblastoma, being more sensitive than contrast-enhanced MRI in subjects with the classic variant [ 49 ].…”
Section: Tumoursmentioning
confidence: 99%
“…An even greater accuracy can be achieved by combining DWI and MRS to obtain more information about the tumour proliferative potential [ 48 ]. DWI has also been reported to be useful in detecting relapse of embryonal tumours such as medulloblastoma, being more sensitive than contrast-enhanced MRI in subjects with the classic variant [ 49 ].…”
Section: Tumoursmentioning
confidence: 99%
“…Diffusion-weighted imaging (DWI) has become established as a standard sequence in neuroradiology. It is extremely valuable in the assessment of tumour cellularity, differential diagnosis and treatment response and in identifying metastases [24][25][26][27]. We recommend 2D echo planar DWI sequence with at least 2 bvalues (b = 0 s/mm 2 and b = 1000 s /mm 2 ).…”
Section: Diffusion-weighted Imagingmentioning
confidence: 99%
“…Whereas the majority of primary embryonic tumors have shown enhancement, the degree of enhancement may be variable, and sometimes absent, with, for example, 11% to 25% of medulloblastomas that do not enhance 24,25 and are variable depending on the molecular subgroup 26 (absence in the subset of group IV 27 ), or some ATRTs. On the other hand, previous studies have shown that medulloblastoma metastases tend to have a lower enhancement than their initial primary lesions, 28 and cancer recurrence was totally unenhanced in 36% of cases, 24 with up to 20% of secondary leptomeningeal diseases missed by conventional MRI but detected by cerebrospinal fluid cytology.…”
Section: Discussionmentioning
confidence: 99%
“…29 This may support the hypothesis of the abstention from GBCA injection during the follow-up of embryonic tumors, which has been developed in a study aiming to reinforce the role of diffusion-weighted imaging for this purpose. 25 However, the embryonic tumors that belong to WHO grade IV are more at risk of recurrence, with worse prognosis, and thus require increased follow-up.…”
Section: Discussionmentioning
confidence: 99%